AB0431 Post-marketing surveillance of tofacitinib in japanese patients with rheumatoid arthritis: an interim report of safety data. (15th June 2017) - Mimori, T; Harigai, M; Atsumi, T; Kuwana, M; Takei, S; Tamura, N; Fujii, T; Matsuno, H; Momohara, S; Yamamoto, K; Kokubo, T; Endo, Y; et al.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). Efficacy and safety of tofacitinib have been shown in RA patients in global Phase 2, Phase 3 (one study included Japanese patients) and long-term extension (LTE) studies and in two Phase 2 and one LTE study in Japanese patients. Objectives: We evaluated the safety of tofacitinib following drug approval in Japanese patients with RA using all-case post-marketing surveillance (PMS) data. Methods: A 6-month interim analysis of safety data from an ongoing 3-year PMS study was conducted (5 Nov 2016 data-cut). All Japanese patients with RA who were treated with tofacitinib were consecutively and prospectively registered in the PMS study and were monitored for all adverse events (AEs) for 3 years. Baseline and follow-up data were collected from booklet-type survey forms. Follow-up surveillance after discontinuation of tofacitinib treatment was implemented: 12 months for serious infections and 3 years for malignancy or AEs leading to death from the date of treatment initiation with tofacitinib. AEs were coded using MedDRA/J. Results: Overall, 2387 tofacitinib-treated patients were enrolled (1020.0 patient-years [pt-yrs] of exposure); of these, 594 patients (24.9%) discontinued treatment, mainly due to AEs (n=236; 9.9%) or lack of effectiveness (n=225; 9.4%). In total, 1793 (75.1%) patients continued treatment for 6 months. At least one AE was observed in 815 patients (34.1%), the most frequent of which was herpes zoster (n=78; 3.3%), including 12 serious cases. Serious AEs occurred in 190 patients (8.0%); the most frequent were pneumonia (n=20; 0.8%), interstitial lung disease (n=14; 0.6%) and condition aggravated (n=13; 0.5%). Infections (n=304; 12.7%) were serious in 88 patients (3.7%). Thirteen patients (0.5%) reported malignancy, including ovarian cancer (n=2; 0.1%), diffuse large B-cell lymphoma (n=2; 0.1%) and lymphoproliferative disorder (n=1, 0.04%). Sixteen (0.7%) deaths were reported. Conclusions: Interim analyses of AEs during the initial 6-month treatment period from PMS reports of tofacitinib in Japanese patients did not reveal any new or unexpected safety signals vs the tofacitinib RA clinical programme. The target sample size for the final PMS analysis is 6000 patients (4000 tofactinib-treated, 2000 control patients). Acknowledgements: This study was sponsored by Pfizer Inc. Editorial support was provided by K Nicholson of CMC and was funded by Pfizer Inc. Disclosure of Interest: T. Mimori Grant/research support from: Astellas, Ayumi, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Nippon Shinyaku, Takeda, Speakers bureau: Astellas, Bristol-Myers Squibb, Chugai, Eisai, Mitsubishi-Tanabe, M. Harigai Grant/research support from: Bristol-Myers Squibb, Eisai, Eli Lilly, Ono, Takeda, T. Atsumi Grant/research support from: Alexion, Astellas, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, Sanofi. Scholarship donations from: Bayer, Daiichi-Sankyo, Takeda, Speakers bureau: AbbVie, Astellas, Chugai, Eisai, Mitsubishi-Tanabe, Pfizer Inc, Takeda, UCB Japan, M. Kuwana Grant/research support from: Chugai, Eisai, Mitsubishi-Tanabe, Ono, Pfizer Inc, Santen, Speakers bureau: Astellas, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, Ono, Pfizer Inc, UCB, S. Takei Grant/research support from: Chugai, Eisai, Mitsubishi-Tanabe, Takeda, Speakers bureau: Asahi Kasei, Ayumi, Chugai, Mitsubishi-Tanabe, Ono, N. Tamura Grant/research support from: AbbVie, Astellas, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, Takeda, Speakers bureau: AbbVie, Astellas, Bristol-Myers Squibb, Eisai, Janssen, Mitsubishi-Tanabe, T. Fujii Grant/research support from: AbbVie, Asahi Kasei, Astellas, Chugai, Eisai, Janssen, Kissei, Mitsubishi-Tanabe, Ono, Pfizer Japan Inc, Taisho Toyama, Takeda, UCB Japan, Speakers bureau: AbbVie, Actelion, Astellas, Ayumi, Chugai, Daiichi-Sankyo, Kissei, Mitsubishi-Tanabe, Nippon Kayaku, Ono, Pfizer Japan Inc, Taisho Toyama, Takeda, H. Matsuno Consultant for: Ayumi, Meiji Seika, Mochida, Nichi-Iko, S. Momohara Speakers bureau: AbbVie, Bristol-Myers Squibb, Eisai, Janssen, Mitsubishi-Tanabe, Ono, Pfizer Japan Inc, Takeda, K. Yamamoto Grant/research support from: AbbVie, Astellas, Ayumi, Chugai, Eisai, Mitsubishi-Tanabe, Nippon Kayaku, Pfizer Japan Inc, Taisho Toyama, Takeda, Teijin, UCB, Speakers bureau: Asahi Kasei, AstraZeneca, Ayumi, Boehringer Ingelheim, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, Pfizer Inc, Sanofi, Sumitomo Dainippon, Taisho Toyama, Takeda, Teijin, Toyama Chemical, UCB, T. Kokubo Employee of: Pfizer Japan Inc, Y. Endo Shareholder of: Pfizer Inc, Employee of: Pfizer Japan Inc, N. Sugiyama Shareholder of: Pfizer Inc, Employee of: Pfizer Japan Inc, T. Hirose Shareholder of: Pfizer Inc, Employee of: Pfizer Japan Inc, Y. Morishima Shareholder of: Pfizer Inc, Employee of: Pfizer Japan Inc, N. Yoshii Shareholder of: Pfizer Inc, Employee of: Pfizer Japan Inc